1987
DOI: 10.1097/00000658-198702000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Takayasuʼs Disease

Abstract: Thirty-nine patients (mean age: 33 years) with Takayasu's disease were observed over the past 8 years. Among these patients, 33 had surgical intervention with a mean follow-up of 4 years. Lesions of the aortic arch were the most common (29 patients, 69 lesions) and frequently were associated with lesions in another site as well. However, in this group of patients, the infrequent presence of signs of cerebral vascular insufficiency limited the number of suitable surgical candidates to 14 patients. Lesions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(72 citation statements)
references
References 11 publications
2
65
0
5
Order By: Relevance
“…The use of angiotensin converting enzyme inhibitors requires careful monitoring in view of the frequency of renal artery stenosis. 31 …”
Section: Treatment Options Medical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of angiotensin converting enzyme inhibitors requires careful monitoring in view of the frequency of renal artery stenosis. 31 …”
Section: Treatment Options Medical Treatmentmentioning
confidence: 99%
“…6 10 Surgery may be unnecessary for aortic arch and splanchnic disease as a result of extensive collateral development. 31 However, recent surgical experience of critical thoracic aortic arch stenoses and stroke risk from the National Institutes of Health, USA 32 33 concluded that critical stenoses should be corrected to prevent stroke, with grafts originating from the ascending aorta. Renal artery involvement is best treated by percutaneous transluminal angioplasty.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Evaluation of disease activity in patients with TA is challenging because clinical features do not correlate with acute-phase reactants in ϳ50% of cases (1)(2)(3), and imaging modalities do not always correlate with clinical and laboratory parameters (4). The complexity of evaluating disease activity in TA is further underlined by the fact that up to 45% of patients in clinical remission have histologic evidence of active disease (1,5).…”
Section: Conclusion Our Findings Indicate That There Is No Associatimentioning
confidence: 99%
“…It may reflect vascular remodeling or atheroma. Alternatively, it could reflect residual inflammation of the arterial wall identified in surgical specimens from patients with clinically inactive disease (1,2). Some of them showed a response to immunosuppressive treatment on the followup scan.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitive and useful method is necessary for the diagnosis of early inflammation and for following disease activity in TA. However, assessment of disease activity in TA is difficult in clinical situations because the clinical symptoms and laboratory parameters do not always adequately reflect the actual inflammation of the arterial wall (1,2), and, as of now, no adequate surrogate is available for assessing disease activity in TA. Imaging modalities such as computed tomography (CT) and magnetic resonance imaging (MRI) reveal anatomic inflammatory changes of the affected arterial wall and have been suggested for mon-itoring disease activity of TA (3), but have not shown consistent correlation with disease activity (4)(5)(6)(7).…”
mentioning
confidence: 99%